Characterization Of Various Types Of Nanofillers Filled Crosslinked Polyethylene Composites For Cable Application - Lim, Kai Sheng (2018)
This research is to study the effect of nanofillers on mechanical, physical, dielectric and thermal properties of the crosslinked polyethylene (XLPE) matrix. Untreated nanofillers used are zinc oxide (ZnO) and aluminium oxide (Al2O3). Treated nanofillers used are organoclay (OMMT), 3-aminopropyltriethoxysilane treated ZnO (KH550-ZnO), triethoxycaprylylsilane treated ZnO (TCS-ZnO) and aluminic ester treated Al2O3 (AE-Al2O3). XLPE nanocomposites were prepared by melt mixing with a single screw extruder followed by hot press moulding. Different weight percentages (0.5, 1, 1.5 and 2 wt%) were compounded in untreated and treated nanocomposites. Combinations of ZnO/Al2O3 and ZnO/OMMT with different ratios (75/25, 50/50 and 25/75) in total of 1 wt% filler loading were compounded in hybrid nanocomposites. Nanocomposites were tested as per ASTM standard methods and characterized with scanning electron microscopy (SEM), thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). The results showed that the addition of untreated and treated nanofillers improved tensile property, burning rate, dielectric property and decomposition temperature. However, it has limited effect on the water resistance property, melting and crystallization temperatures. The optimal filler loading was 1.5 wt% and the effect of Al2O3 is better than ZnO and OMMT nanofillers based on most properties. Surface treatment with coupling agent enhanced the interface between the filler and the matrix with chemical bonding. Strong filler-matrix interaction further improved the properties of composite. The optimal filler loading was 1.5 wt% and the effect of AE-Al2O3 is better than KH550- ZnO and TCS-ZnO nanofillers based on most properties. In hybrid nanocomposites, the best filler ratio was 50/50 in ZnO/Al2O3 and 75/25 in ZnO/OMMT combinations which induced synergistic properties. Overall, AE-Al2O3(1.5)/XLPE nanocomposite has the best results. As compared with the unfilled XLPE, it has led to the significant improvement in tensile strength (59%), elongation at break (51%), Young’s modulus (60%), contact angle (4%), dielectric breakdown strength (35%), volume resistivity (55%), decomposition temperature and reduced burning rate (14%). It is suitable for cable insulation application due to its extraordinary mechanical, physical, dielectric and thermal properties.